Achievement Motivation and Parenting Styles in Promoting Effective Learning Among Secondary School Students in Ondo State - Florence O., Ojewola; Yinusa A., Faremi (European Scientific Journal, ESJ, 2018)
Effective learning among secondary school students in Ondo state has become a source of concern to all well-meaning people in the educational sector hence this study investigated achievement motivation and parenting styles in promoting effective learning among secondary school students in Ondo State. Descriptive survey design was adopted for this study. The sample was made up of 245 secondary school students randomly selected from five local government areas in Ondo state. A questionnaire titled Assessment of Secondary School Students Academic Achievement Motivation for Promoting Learning. Questionnaire was administered on the students to assess their achievement motivation and parenting styles in enhancing effective learning among secondary school students. Data collected were analysed using Analysis of Variance and t-test. The three null hypotheses formulated were tested at 0.05 alpha level. The results revealed that there was no significant difference between academic achievement motivation and parenting styles of secondary school students. The other two hypotheses based on family structure and gender were not rejected. It was concluded that achievement motivation and the styles adopted by parents in raising their children may not have any impact on the secondary school students’ effective learning outcome. It was also recommended among others that teachers and parents should make their students to develop achievement motivation.